Coordination and harmonization of national & regional public sector modernization initiatives in CARICOM member states : a concept paper - Jones, Edwin (CARICAD [St. Michael]BB, 2006)
Provides some insights and guidance about the construction and delivery of an agenda about current problems of administrative modernization/reform congruent with Caribbean values, visions, experiences, as well as theory relevant to challenges of coordination and harmonization of initiatives.